Activation of Toll-Like Receptors Differentially Modulates Inflammation in the Human Reproductive Tract: Preliminary Findings - Benjelloun, Fahd; Quillay, Héloïse; Cannou, Claude; Marlin, Romain; Madec, Yoann; Fernandez, Hervé; Chrétien, Fabrice; Le Grand, Roger; Barré-Sinoussi, Françoise; Nugeyre, Marie-Thérèse; Menu, Elisabeth (Frontiers in Immunology, 2020)
The female reproductive tract (FRT) is the main site of entry of sexually transmitted infections (STIs). Toll-Like receptors (TLRs) that recognize pathogenic motifs are widely expressed in the FRT. TLR stimulation induces immune activation and local production of inflammatory mediators. In the FRT, this response should also be compatible with reproductive functions and symbiosis with host microbiota . With a view to develop efficient mucosal vaccines to prevent STI acquisition, the role of TLR ligands in the FRT needs to be explored. We have therefore investigated the cytokine profiles of the different compartments of the FRT (vagina, endocervix, ectocervix and uterus) before and after stimulation of mononuclear cells from human tissue specimens. The comparison with PBMCs allowed us to highlight the FRT specificities. We first characterized the main immune cell populations in each compartment and observed that their distribution was different through the compartments. The CD45+ cells represented a maximum of 11% in the FRT in contrast to 96% in PBMCs. We identified two main populations among the CD45+ cells in the four compartments of the FRT: CD3+ T cells (CD4+ and CD8+) and CD14+ APCs. B cell populations (CD19+) were much less frequent than T cells in all the FRT regions and were equally distributed. NK CD56+ cells were detected in all compartments and were more abundant in the uterus. Stimulation of the mononuclear cells was then performed with TLR agonists: R848 for TLR7/8, Poly I:C for TLR3, LPS for TLR4 and ODN CpG for TLR9. Cytokine levels in unstimulated cultures of cells isolated from all FRT compartments were higher than in cultures of unstimulated PBMCs. In contrast, after stimulation with TLR agonists, cytokine responses induced by TLR agonists were moderate in the FRT and significantly lower than in PBMCs. These responses were varied with different TLR ligands and FRT compartments. The cytokine profile induced by TLR activation in the FRT supports the role of these tissues in genital anti-microbial immunity and in the control of inflammation while allowing maintenance of its reproductive function.